Barriers to flexible sigmoidoscopy colorectal cancer screening in low uptake socio‐demographic groups: A systematic review. Issue 8 (7th July 2020) - Travis, Elizabeth; Ashley, Laura; Pownall, Madeleine; O'Connor, Daryl B.
Abstract: Objective: To synthesise qualitative evidence related to barriers and facilitators of flexible sigmoidoscopy screening (FSS) intention and uptake, particularly within low socio‐demographic uptake groups. FSS uptake is lower amongst women, lower socio‐economic status (SES), and Asian ethnic groups within the United Kingdom (UK) and United States of America. Methods: A total of 12 168 articles were identified from searches of four databases: EMBASE, MEDLINE, PsycINFO and Web of Science. Eligibility criteria included: individuals eligible to attend FSS and empirical peer‐reviewed studies that analysed qualitative data. The Critical Appraisal Skills Program tool evaluated the methodological quality of included studies, and thematic synthesis was used to analyse the data. Results: Ten qualitative studies met the inclusion criteria. Key barriers to FSS intention and uptake centred upon procedural anxieties. Women, including UK Asian women, reported shame and embarrassment, anticipated pain, perforation risk, and test preparation difficulties to elevate anxiety levels. Religious and cultural‐influenced health beliefs amongst UK Asian groups were reported to inhibit FSS intention and uptake. Competing priorities, such as caring commitments, particularly impeded women's ability to attend certain FSS appointments. The review identified a knowledge gap concerning factors especially associated with FSS participation amongst lower SES groups. Conclusions: Studies mostly focussed on barriers and facilitators of intention to participate in FSS, particularly within UK Asian groups. To determine the barriers associated with FSS uptake, and further understand how screening intention translates to behaviour, it is important that future qualitative research is equally directed towards factors associated with screening behaviour.